Does interspecific competition have a moderating effect on Taenia solium transmission dynamics in Southeast Asia? - Conlan, J; Vongxay, K; Fenwick, S; Blacksell, S; Thompson, R (2009)
It is well understood that sociocultural practices strongly influence Taenia solium transmission; however, the extent to which interspecific parasite competition moderates Taenia transmission has yet to be determined. This is certainly the case in Southeast Asia where T. solium faces competition in both the definitive host (people) and the intermediate host (pigs). In people, adult worms of T. solium, T. saginata and T. asiatica compete through density-dependent crowding mechanisms. In pigs, metacestodes of T. solium, T. hydatigena and T. asiatica compete through density-dependent immune-mediated interactions. Here, we describe the biological and epidemiological implications of Taenia competition and propose that interspecific competition has a moderating effect on the transmission dynamics of T. solium in the region. Furthermore, we argue that this competitive ecological scenario should be considered in future research and surveillance activities examining T. solium cysticercosis and taeniasis in Southeast Asia.